Cellular development of the germinal epithelium during the female and male gametogenesis of Chaetodon striatus (Perciformes: Chaetodontidae) - Bayona Perez, Isabelle Leite [UNESP]; Mazzoni, Talita Sarah; Quagio-Grassiotto, Irani [UNESP] (Cambridge University Press (CUP), 2020)
SummaryButterflyfish Chaetodon striatus is highly sought after in the marine ornamental aquarium, although studies about its reproductive biology are scarce. Therefore, to contribute to a better understanding of the reproductive aspects of C. striatus, we describe in detail with the use of high resolution histology the cellular dynamics of the germinal epithelium during the reproductive life history of this species. Based on the activity of the germinal epithelium, this study describes different stages of the gonadal development, similar to the reproductive phases found in other fish, to determine the reproductive period of C. striatus. In characterization of gonadal development, the following germ cells are described for males: spermatogonia, spermatocytes, spermatids and spermatozoa. Oogonia, early, primary, secondary, full-grown and maturing oocytes are described for females. Female germinal epithelium of C. striatus showed substantial changes over the study period, indicating that there was an active spawning period. Male germinal epithelium also presented relevant alterations, indicating reproductive activity in the testicular lobules. Morphological data confirm how informative was the cellular dynamics of the germinal epithelium for understanding gonadal development during adult reproductive life of fish in general. Although Chaetodon are a popular species, previous studies have only produced superficial and rough histological analyses. Therefore, this study demonstrates important information on germinal epithelium of Chaetodon. This knowledge could be a fundamental tool for development of new strategies for breeding of several species in captivity, especially butterflyfishes.
Keywords: Butterflyfish; Gonadal morphology; Keywords:; Oogenesis; Reproductive biology; Spermatogenesis